Reverse 1-center problem on weighted trees. (2nd January 2016) - Nguyen, Kien Trung
Abstract : This paper addresses the reverse 1-center problem on a weighted tree. Here, a facility has already been located in a predetermined node of the tree network and we want to improve the 1-center objective value at that node as efficiently as possible within a given budget. For solving this problem under uniform linear cost functions, we develop a combinatorial algorithm with running time, where is the number of vertices of the tree.